THE DEMOGRAPHIC DIVIDEND IN SUB-SAHARAN AFRICA: TWO ISSUES THAT NEED MORE ATTENTION. (13th February 2017) - May, John F.; Turbat, Vincent
Abstract: In mid-2016, the population of Sub-Saharan Africa (SSA) was almost 1 billion people. By 2050, the population of the region will probably reach 2.1 billion people [Population Reference Bureau (2016 )]. In 2100, SSA's population could be almost 4 billion people [United Nations (2015 )]. This rapid demographic increase would translate into a possible quadrupling of the current SSA population by the end of the century (unless fertility would decline sharply in the near future). Nonetheless, the region has embarked on its demographic transition, i.e., the shift from high to low crude birth rates and crude death rates, albeit this process has occurred in SSA at a slower pace than in the rest of the developing world. In particular, the decline of fertility has been slower in SSA than in the other regions of the world. The rapid population growth and the occurrence of a demographic transition in the region have generated discussions on the prospects for SSA to open a demographic window of opportunity and capture a first demographic dividend. However, two crucial dimensions, which have so far been rather neglected, need more attention. First, one will need to define with more accuracy the sub-populations of the working-age adults and their young and older dependents, therefore refining the calculation of the dependency ratio. In particular, one will need to assess the population of the young dependents as well as the population of adults who are actually working. Second, it will be also necessary to examine the conditions required to trigger a faster and significant fertility decline in the region. This is most important because the relationship between the active adults and their dependents is predicated by the fertility decline, which will bring the changes to the age structure.